Synthesis of Heteroaromatic Compounds (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue, entitled the “Synthesis of Heteroaromatic Compounds”, is an outstanding collection of fourteen original research papers and six review articles that discuss the advances made in both conventional and green preparatory methods, as well as the properties and applications of heteroaromatic molecules in industrial and medicinal chemistry areas of study.The collected works featured herein collate contributions from a truly international and diverse array of ninety experts in the fields of heteroaromatic compound synthesis, QSAR studies, computational chemistry and molecular docking, as well as bioactivity studies.